PENGARUH MODEL TALKING STICK DALAM HASIL BELAJAR SISWA MATA PELAJARAN PENDIDIKAN PANCASILA DI SEKOLAH DASAR - Jannah, Richmatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the effect of the talking stick learning model on the learning outcomes of Pancasila education subjects for class III students at SD Negeri 2 Suko Sidoarjo Sidoarjo, namely that there is a problem of low student learning outcomes in learning on Pancasila education subjects. The research population was 25 students. This research used a descriptive qualitative type method in class III of SD Negeri 2 Suko Sidoarjo Sidoarjo. Based on the results of the analysis of student response questionnaires, it can be concluded that students provide positive responses to learning using a qualitative descriptive analysis technique approach. This is reinforced by the results of interviews which state that students are interested in learning using the talking stick method. The results of qualitative descriptive research show that the use of the talking stick learning method can be seen from the results of increasing the percentage of learning completion for class III students at SD Negeri 2 Suko Sidoarjo Sidoarjo. The average pre-cycle value was 63.8 or 60%, Cycle I was 70.4 or 80%, and Cycle II was 76.4 or 96%.